ENVIRONMENTAL PROBLEMS, RECYCLING, AND CLIMATE CHANGE THESIS STATEMENT - Raxmatjonov Muhammadaziz; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Annotation:This paper examines the escalating severity of global environmental problems—most  critically  climate  change—driven  primarily  by  anthropogenic greenhouse  gas  emissions.  It  explains  the  interconnected  challenges  of  resource depletion, pollution, and biodiversity loss, while emphasizing the centrality of climate change as a planetary crisis. The study evaluates the role of recycling and the circular economy  as  essential  but  insufficient  responses  within  a  broader  sustainability framework.  Through  analysis  of  contemporary  scientific  assessments  and international  reports,  including  those  of  the  IPCC,  UNEP,  OECD,  and  the  Ellen MacArthur Foundation, the paper argues that recycling and resource-loop systems can significantly reduce environmental pressure but cannot independently resolve the climate crisis. The conclusion stresses that meaningful progress requires an urgent global transition to renewable energy, strong governance, systemic economic reform, and a collective societal shift toward sustainable consumption. Only a coordinated, holistic strategy can prevent irreversible ecological and socioeconomic consequences for humanity.